Nilai Moral Pada Karya Tari “Dosa dibalas Dosa” - Tarindo, Tarindo (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to provide moral values in the dance work “Dosa dibalas Dosa”, a dance work inspired by the Indonesian cinema film entitled “Tuhan Izinkan Aku Berdosa”directed by Hanung Bramantyo, and packaged with a shorter version of the story. The method used in this research is a qualitative method with a descriptive approach. Data was collected by reading the story line of the dance work “Dosa dibalas Dosa” which was written by the creator of the dance work or choreographer. The results of the research show that the dance work “Dosa dibalas Dosa” has moral values which can be used as a moral Lessons for the audience of the dance performance or for readers of the story line of the dance work. The moral values contained in the dance work “Dosa dibalas Dosa” include, Honesty, Courage and Justice. In conclusion, the dance work “Dosa dibalas Dosa” not only talks about violence and sexual harassment, but also talks about characters who are brave, honest, fair and responsible, which can be a moral message for the audience of the performance and for people who read the storyline of the work.